A educação física no ciclo II do ensino fundamental : refletindo sobre indicadores educacionais de desenvolvimento profissional da docência com um professor experiente - Leal, Paulo Henrique (2011)
Throughout this dialogue we fetch describe and analyze the conceptions of an experienced teacher of Physical Education on Knowledge Teacher and about what, why and to what degree of proficiency of their students 3rd and 4th grades of Elementary School in a State School in São Paulo State, should know about physical education in their classrooms. For this, we rely on the following question: What, why and to what extent an experienced physical education teacher should know about the content in order to teach their students? And what, why and to what extent students Cycle II (3rd and 4th grades) of elementary school should know about this content? We keep the term "grades" because the school itself, at the time that there was monitoring, the nomenclature used for classes and, therefore, we recognize and value their provisions and curricular structures. Linked to the apprehension of these objectives also aim to perform analysis on educational indicators of professional development in teaching, which, emphasizing the processes of teaching and learning at school, could tell us, from the participant's response, aspects of the professional development of physical education teacher in their work context. In light of qualitative research, we used the technique to collect the semi structured interview. And to best to approach the phenomenon investigated, in addition to interviews, we conducted systematic visits to meet the participant's work context. We found that teachers have a profession that is eminently collective, but that also requires personal commitment and dedication, which indicates the need for autonomy and professional responsibility. As demonstrated by the participating teacher, professional development in teaching is an inherent element of the qualified performance in Physical Education as much sway over what each teacher intends to teach classes throughout the school. Beyond this specific area, we see it necessary for the Physical Education teacher to develop different strategies, using diverse methodologies and examples, optimize time and expand the opportunities for learning environments related to students' everyday life in and out of school, mobilize knowledge to that every child, every learner to appropriate the culture of body movement in a critical, independent and conscious. Amid all this process, it is the school community as a whole promotes opportunities, facilities and adequate periods for the development of teaching process, learning and teacher professional development. So it's important to establish analytical criteria, parameters and indicators that provide information contextualized these procedural elements.